2001
DOI: 10.1136/pmj.77.908.399
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microalbuminuria in type 2 diabetes mellitus at a diabetes centre in southern India

Abstract: Objective-The aim of this study was to determine the prevalence and risk factors for microalbuminuria among south Indian type 2 diabetic patients attending a diabetes centre. Methods-One thousand four hundred and twenty five type 2 diabetic patients attending a diabetes centre in south India were recruited for the study. Urinary albumin concentration was measured by immunoturbodimetric assay. Microalbuminuria was diagnosed if the urinary albumin excretion was >30 mg/g of creatinine. Results-Overall prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
128
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(164 citation statements)
references
References 30 publications
34
128
2
Order By: Relevance
“…13 K. G Santosh et al, have shown that glycosylated hemoglobin, MA and the duration of diabetes mellitus were independently related to DR. 14 In our research study, HbA1c and MA in diabetic patients with DR were positively correlated, which was similar to the findings reported by some previous study. [15][16][17][18] In another study, there was no significant association of MA with HbA1c, but there was a strong association with fasting blood glucose, which was similar to an earlier study. 19 Poor glycemic control (HbA1c) is a risk factor of MA.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…13 K. G Santosh et al, have shown that glycosylated hemoglobin, MA and the duration of diabetes mellitus were independently related to DR. 14 In our research study, HbA1c and MA in diabetic patients with DR were positively correlated, which was similar to the findings reported by some previous study. [15][16][17][18] In another study, there was no significant association of MA with HbA1c, but there was a strong association with fasting blood glucose, which was similar to an earlier study. 19 Poor glycemic control (HbA1c) is a risk factor of MA.…”
Section: Discussionsupporting
confidence: 74%
“…12 there is a significant statistical correlation between the prevalence of MA and the presence of diabetic retinopathy. [21][22][23] …”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of microalbuminuria was not statistically different from the males and females. The similar study was conducted in India by Varghese et al reported an increased prevalence of microalbuminuria in Indian men compared with Indian women [9]. In our study, there was statistically significant difference in FBS and postprandial blood sugar in both groups.…”
Section: Geetha and Shanmugasundaramsupporting
confidence: 73%
“…Previous studies have also shown positive correlation of microalbuminuria with the age of Type 2 diabetes patients [13,14]. A similar study conducted by Varghese et al reported that there was statistical correlation was found between microalbuminuria and age [9]. Our study has shown significant differences between both groups in baseline characteristics of BMI and but the correlation between microalbuminuria and BMI was not seen.…”
Section: Geetha and Shanmugasundaramcontrasting
confidence: 41%
“…Expected protein excretion was calculated by the protein/ creatinine ratio method and overt proteinuria was defined as Z300 mg/day. 27 …”
Section: Biochemical Estimationsmentioning
confidence: 99%